Crenças de futuros professores de português sobre leitura e seu ensino - Luz, Leandro Tadeu Alves da (2015)
This study has its focus on the initial formation of Portuguese teachers. It aims at investigating the beliefs of future teachers about reading and its teaching. The theoretical basis of this study is, therefore, knowledge of the researches about teachers formation; besides studies about reading and literacy and also the theories about beliefs. The data to be analyzed were collected in a course of Letras from a private university of São Paulo. The subjects, altogether 45, are students from the last two semesters of the course. To collect the data, the following instruments were used: discussions in format of focal group, autobiographic narratives, beliefs inventory and interviews. The main instrument, especially elaborated to this thesis, thus unpublished, was an inventory of beliefs about reading and its teaching, composed by 67 assertions, divided into 12 categories and an open question, beyond a questionnaire with personal information from the subjects. This inventory was elaborated from the information raised in the focal groups and in the autobiographic narratives; and the responses were discussed in the interviews. It was possible to realize, through the data analysis, that there is a strong presence of beliefs about reading and its teaching in these research subjects. For being future Portuguese teachers, this fact gains special importance, because these students will give classes, one day, and they will do it based not only upon what they learnt in their teaching course, but also upon what they have learnt throughout their lives in contact with school. They will teach, in other words, not only based on their theories, but also based on their beliefs